Escherichia Coli Removal from Water Using Electrophotocatalytic Method - A Rezaee; Kashi A Jonidi-Jafari; AR Khataee; A Nili-Ahmadabadi (Journal of Applied Sciences and Environmental Management)
Electrochemical has the suitable method of drinking water disinfection. This method leads to production of hydroxyl radicals which are known powerfull oxidant agent. In recent years, water disinfection using electrophotocatalytic method is spreading. The aim of this experimental applied study is to evaluate the removal of Escherichia Coli, as the microbial contamination indicator of water, from drinking water using electrophotocatalytic method. The contaminated water in an electrophotocatalytic reactor were prepared by adding 102-103 cell of E. coli bacteria to drinking water. The studied variables were pH (6-8), the number of bacterial suspensions (102-103 cells / ml), the UV-A lamps (2-4 W), times (5-40 min), the distances between electrodes (2-3.5 cm), layering of zinc oxide nanoparticles (1-3), and voltages (10-40). The findings showed the correlation between removal of cells and UV-A lamps, voltage, and time of electrolysis. Optimal removal (MPN: 0) was obtained at pH 8, time of electrolysis: 5 minutes, 2 layer of nano ZnO, and voltage of 10 V. This result offers that this method is an efficient method for water disinfection. @JASEM